2007
DOI: 10.1068/c1312r
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Landscapes in Hospital Design: A Qualitative Assessment by Staff and Service Users of the Design of a New Mental Health Inpatient Unit

Abstract: This pilot research project sought to provide a postoccupation assessment of a new mental health inpatient unit in East London, built under the Private Finance Initiative scheme. Qualitative discussion groups or unstructured interviews were used to explore the views of people who had been service users (but were currently well) and of nursing staff and consultants working in the new hospital. The participants gave their views on the aspects of the hospital which were beneficial or detrimental to well-being and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
137
1
12

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(153 citation statements)
references
References 39 publications
3
137
1
12
Order By: Relevance
“…example, experimental research in Finland using a perceived restorativeness scale (PRS), identified a range of specific places, including those associated with water, that were associated with improved wellbeing (Korpela and Hartig, 1996). By providing evidence of their curative efficacy, such green/ blue space elements became influential in the design of formal and informal care settings such as hospitals, clinics and retreats as well as in wider urban design (Kaplan, 1995;Gesler et al, 2004;Conradson, 2005aConradson, , 2005bCurtis et al, 2007). Different forms of water -still, flowing, raging, spiritually charged -were additional built components, particularly in retreat, CAM and contemporary spa settings (Conradson, 2007;Hoyez, 2007;Lea, 2008;Foley, 2010;Little, 2013).…”
Section: Writing Healthy Blue Spacementioning
confidence: 99%
“…example, experimental research in Finland using a perceived restorativeness scale (PRS), identified a range of specific places, including those associated with water, that were associated with improved wellbeing (Korpela and Hartig, 1996). By providing evidence of their curative efficacy, such green/ blue space elements became influential in the design of formal and informal care settings such as hospitals, clinics and retreats as well as in wider urban design (Kaplan, 1995;Gesler et al, 2004;Conradson, 2005aConradson, , 2005bCurtis et al, 2007). Different forms of water -still, flowing, raging, spiritually charged -were additional built components, particularly in retreat, CAM and contemporary spa settings (Conradson, 2007;Hoyez, 2007;Lea, 2008;Foley, 2010;Little, 2013).…”
Section: Writing Healthy Blue Spacementioning
confidence: 99%
“…The approach used to conduct the research was based on similar techniques that had been trialled previously (Curtis et al, 2007(Curtis et al, & 2008 Hospital or the General Hospital) were good or bad for the wellbeing of people using the facilities. We were able to talk to some informants twice; once before and once after psychiatric services were moved to the New Hospital.…”
Section: Context and Methodsmentioning
confidence: 99%
“…We consider how this dynamic perspective contributes to ideas about psychiatric hospitals as 'therapeutic landscapes' (Gesler et al, 2004;Campling et al, 2004;Curtis et al, 2007;Karlin & Zeiss, 2006;Ruane, 2004;Schweitzer et al, 2004), which are not only 'clinically efficient' but also offer physical, social and symbolic features that are beneficial for one's sense of wellbeing and therefore help to promote healing in a more holistic sense. Brown (2003, p. 490) suggests that 'health care facilities hold a position of symbolic significance within their localities' and that 'the sense of ownership' by the community is important for the way they are perceived.…”
Section: Introductionmentioning
confidence: 99%
“…Government ministers, NHS planners and managers, architects, and hospital staff and patients participated in designing new facilities, raising hopes for improved care (Gesler et al 2004). Studies of individual hospitals have assessed to what extent these hopes were realized (Quirk et al 2006, Curtis et al 2007). Here we make an original contribution to these evaluations by exploring the emotional experiences of staff and informal carers, as well as patients affected by these changes.…”
Section: From Old To New: Re-provisioning the Psychiatric Hospitalmentioning
confidence: 99%
“…Places constituting a therapeutic landscape may include medical settings for care of serious mental illness, where the therapeutic experiences of patients can be influenced by attributes of the built infrastructure, relationships that patients experience and the meanings they attribute to these aspects of the caring environment (Curtis et al 2007;Gesler et al 2004; Author et al…”
Section: Introductionmentioning
confidence: 99%